Effectiveness of Aloe Vera Extract in Reducing Formalin Levels in Catfish Fillets (Pangasius sp.) - Setiawati, Risa Fuji; Kurnia Hartati, Fadjar; Susilo, Achmadi; Hariyani, Nunuk; Rahmiati, Retnani (CV. Media Digital Publikasi Indonesia, 2024)
This study used a quantitative experimental laboratory method with a research design. Completely Randomized Design (CRD) with treatments K0B0, K1B1, K1B2, K1B3, K2B1, K2B2 and K2B3. The research variables include chemical quality tests, namely formalin levels, protein levels and organoleptic tests (appearance, aroma and texture) with 3 replications in each treatment using 25 panelists. The purpose of this study was to determine which treatment can reduce formalin content, maintain protein levels and organoleptic values ​​of catfish fillets. The treatment that can reduce the highest formalin levels and increase the highest protein levels is the K2B3 treatment with a percentage decrease in formalin levels of 82,339% and an increase in protein levels with a percentage increase of 48.128%. Based on the results of the organoleptic test, the best appearance was produced in treatments K1B1 and K2B1 with a median of 7 which means the color is specific to the type and less bright. The best aroma was produced by treatments K1B1, K1B2, K2B1 and K2B2 with a median of 5 which means musty and slightly rancid. The best texture was produced by treatments K1B1 and K2B2 with a median of 7 which means dense, less compact and less elastic